RELEVANSI KITAB BIDAYATUL HIDAYAH DALAM MENGINTERNALISASIKAN NILAI-NILAI AKHLAK DI ERA NEW NORMAL - Chauzarani Rozaki; Muhammad Anas Ma'arif (FKDP (Forum Komunikasi Dosen Peneliti), 2022)
This research was conducted to determine the moral values in the Bidayatul Hidayah book and to determine the relevance of the Bidayatul Hidayah book in the New Normal era. This is because morality is the most important factor that is used as a guide in life, especially in the New Normal era which currently appears various kinds of problems that make it difficult for humans to live life. So to achieve this goal, the researcher uses a qualitative method with a Library Research approach which in finding research data is contained in books and books by using content analysis. The results of this study are the relevance of the book of Bidayatul Hidayah in internalizing morality in the New Normal era and many moral values are found, so they are good to apply in life. such as religious, family, economic, social, and educational fields. Although there are some values that are less relevant to be applied in the New Normal era, such as honoring guests, conducting gatherings, and ta'dzib to a teacher. This is because in this era interaction activities are carried out online and are limited in nature in order to break the spread of the Covid-19 virus.